Original articlePercutaneous closure of patent foramen ovale after neurological decompression illness in divers - Kłopotowski, Mariusz; Demkow, Marcin; Konka, Marek; Dzielińska, Zofia; Juraszyński, Zbigniew; Rużyłło, Witold (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2008)
Background: Patent foramen ovale (PFO) has been associated with increased risk of cerebral neurological decompression illness (DCI). Percutaneous PFO closure in divers with “unexplained” neurological DCI seems to prevent recurrence of such complication, but evidence supporting this strategy is very limited. Aim: Does percutaneous PFO closure prevent the recurrence of cerebral neurological decompression illness in divers? Methods: Five divers with cerebral neurological decompression illness, who underwent percutaneous PFO closure, were observed. Two were professional divers. All divers fulfilled safe diving profiles both before and after the procedure. PFO closure was performed under general anesthesia with transoesophageal echocardiography monitoring. Data regarding diving profile after PFO closure were collected during direct interview with patients. Results: Median follow-up was 22 months (minimum 6 months, maximum 78 months). During this period none of the divers experienced neurological decompression illness. A total number of about 1450 dives was performed (first diver about 1200 dives, second – 32, third – 80, fourth – 104, and fifth – 35). All patients achieved greater maximum diving depths than before PFO closure (first diver 160 m, second – 85 m, third – 55 m, fourth – 70 m, and fifth – 36 m). Conclusions: Percutaneous PFO closure prevents recurrence of cerebral neurological decompression illness among divers, who keep rules of good diving practice.